The development of green infrastructure concept within Slovenian spatial planning practice - PENKO SEIDL, Nadja (Sciences, Eaux & Territoires, 2021)
The term "green infrastructure" was established at the end of the 20th century in the United States and Western Europe. The concept itself has evolved over time in response to environmental problems. It addresses planning issues by combining landscape and ecological planning methods with knowledge of natural and social systems. Drawing on Slovenian case studies, this paper aims to understand the ability of the Green Infrastructure concept to operate across scales, disciplines and administrative boundaries.